Differential diagnoses of MS in clinical practice: incidence and methods for differential diagnosis - Steinberg, Tim Johannes; Mayer, Lucie; Freudenstein, David; Müller, Karolina; Angstwurm, Klemens; Linker, Ralf A.; Lee, De-Hyung (Frontiers in Neurology, 2025)
Background and objectivesThe diagnosis of multiple sclerosis (MS) is based on the McDonald diagnostic criteria and the exclusion of relevant differential diagnoses. This study aimed to determine the relative frequencies of MS differential diagnoses and to identify which diagnostic measures are most effective in distinguishing those from one another.MethodsWe conducted a retrospective analysis of all cases treated in the neurology ward of the University Hospital Regensburg during the years 2019 and 2020. The inclusion criteria comprised cases presenting with subacute focal neurological symptoms accompanied by corresponding lesions on magnetic resonance imaging (MRI) that could not be primarily attributed to MS, tumor, hemorrhage, or ischemia, as well as cases with abnormal external MRI findings who were referred to our clinic for the evaluation or exclusion of multiple sclerosis.ResultsA total of 127 cases were included in the study. Differential diagnoses of MS were predominantly of inflammatory or vascular origins or non-specific white matter lesions. The primary diagnostic tools for distinguishing differential diagnoses of MS from one another were patient history (fever), cerebrospinal fluid analysis, and brain MRI, as well as a duplex ultrasound of the cranial vessels.DiscussionOur study demonstrates that cerebrospinal fluid analysis and brain MRI are essential not only for the diagnosis of MS but also for distinguishing among its various differential diagnoses. In particular, duplex ultrasound may assist in identifying vascular lesions, while the presence of fever may suggest an infectious cause.